Assessment of fatigue life and reliability of high-mast luminaire structures. (July 2020) - Tsai, Li-Wei; Alipour, Alice
Abstract: Recent failures of high-mast luminaire poles have showcased the vulnerability of such structures to wind loading. High mast luminaire poles are long slender structures with low damping and highly susceptible to wind-induced vibrations that over a large number of cycles can result in fatigue failures during the life cycle of the structure. Such poles are constructed from sets of components that include base plate, reinforced cut-out hand holes, weld details and a hollow tubular pole supporting the luminaire. Among all these components, the base-to-tube connection was identified to have the lowest fatigue resistance through static analysis and previous fatigue experiments, so this study focuses on estimating the fatigue life of the base-to-tube connection under wind loading. Wind time histories were generated for different mean wind speeds and used to analyze fatigue performance in terms of stress cycle, failure, and damage indices. Simulated results were collected to build a damage fraction function to show the fatigue damage created in a certain period at different mean wind speeds. Local wind probability data was combined with the fatigue damage fraction function to estimate the fatigue life at different locations. Also, reliability analysis was carried out through running Monte Carlo simulations. The results provide a general framework for helping designers and fabricators to better determine the fatigue life and probability of failure of high-mast luminaire poles. Highlights: A framework to assess fatigue life and reliability of high mast luminaire structures. Monte Carlo simulation is used to estimate the probability of failure. Reliability analysis has been conducted for three cities in Iowa. The framework can be used on other structures having fatigue damage due to wind. Estimated reliability can be used to determine the maintenance period.